Persuasión por la palabra: discurso y belleza - Casado Velarde, Manuel (Mercurio Peruano, 2013)
Words can not only persuade us, but also seduce us. Manipulations of language have always existed and modern times have created distrust in discourse. But all this has not been able to banish the “nostalgia of the origins” which is present in the ordinary speech activity, in the classical thought and in the poetry of all time, that is, an experience-based conviction that “the names we give to things suit them for some reason” (Covarrubias). The recovery of the vigour of language is achieved through the cancellation of the existing fissures between the person and his/her speech, between truth and beauty, between the good and the beautiful. But perhaps this goal cannot be achieved if we renounce the Word and Beauty.
Keywords: discourse, manipulation, persuasion, trust and suspicion, language and truth, discourse and beauty.